2009
DOI: 10.1134/s1070428009120185
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 3-chloro-1-(2,4,6-trimethylphenyl)propan-2-one with amines

Abstract: SHORT COMMUNICATIONSWhile continuing our studies in the fields of synthesis and transformations of 1,2-chlorohydrins [1] obtained by reaction of arenes with 3-chloro-1,2-epoxypropane in the presence of aluminum chloride, we performed oxidation of 3-chloro-1-(2,4,6-trimethylphenyl)propan-2-ol (I) with chromium(VI) oxide and isolated 3-chloro-1-(2,4,6-trimethylphenyl)propan-2one (II). α-Chloro ketone II was brought into reaction with various primary amines in aqueous potassium hydroxide at room temperature. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…A recent study reported the reaction of 1-chloro-3-(2,4,6-trimethylphenyl)propan-2-one and primary amines. The chlorine atom in the α-chloro ketone is not replaced directly by the amino RNH-group; the intermediate product undergoes a Favorskii rearrangement that furnishes a compound having two methylene groups between the aromatic system and the amido unit (Yadigarov et al, 2010). A recent study used thiourea as the amino reactant (Maharramov et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported the reaction of 1-chloro-3-(2,4,6-trimethylphenyl)propan-2-one and primary amines. The chlorine atom in the α-chloro ketone is not replaced directly by the amino RNH-group; the intermediate product undergoes a Favorskii rearrangement that furnishes a compound having two methylene groups between the aromatic system and the amido unit (Yadigarov et al, 2010). A recent study used thiourea as the amino reactant (Maharramov et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…For background to the synthesis: see: Yadigarov et al (2010). For the structure of tolperisone hydrochloride, see: Tanaka & Hirayama (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…The chlorine atom in the α-chloro ketone is not replaced directly by an amino RNH-group. The intermediate product undergoes a Favorskii rearrangement that furnishes a compound having two methylene groups between the aromatic system and the amido unit (Yadigarov et al, 2010). The present study employs thiourea as the amine.…”
Section: Data Collectionmentioning
confidence: 99%
“…For background to the synthesis: see: Yadigarov et al (2010). For the structure of 1-(piperidin-1-yl)-3-(2,4,6-trimethylphenyl)propan-2-ol, see: Maharramov et al (2011).…”
Section: Related Literaturementioning
confidence: 99%
“…A recent study reported the reaction of 1-chloro-3-(2,4,6-trimethylphenyl)propan-2-one and primary amines. The chlorine atom in the α-chloro ketone is not replaced directly by the amino RNH-group; the intermediate product undergoes a Favorskii rearrangement that furnishes a compound having two methylene groups between the aromatic system and the amido unit (Yadigarov et al, 2010). A recent study used cyclic secondary amine as the amino reactant in the synthesis of a compound having a formulation similar to that of tolperisone (a piperidine derivative that is commercially used as a muscle relaxant) (Maharramov et al 2011).…”
Section: Data Collectionmentioning
confidence: 99%